The Percentage Of Mechanical Launch Variables Contribution On Long Jump Achievement In U20 Jumpers - Khalil, Athear (Journal of Physical Education, 2016)
The problem of the research lies in finding the contribution percentage of launch variable in long jumpers U20 as well as not paying enough attention learning and training for achievement. The aim of the research is to identify the values of mechanical launch variables in long jump as well as indentifying the percent of these variables contribution in achievement. The researcher filmed long jumpers with high speed cameras to come up with the mechanical launch variables. The subjects were 10 under 20 long jumpers from Athletics gifted care center/ ministry of Sports And Youth. After motor analysis, the mean and standard deviation were calculated to find the correlation value and contribution percentage. In addition to that the results helped in identifying which variables are more suitable with achievement. The researcher concluded that the percentage of contribution did affect achievement especially in pushing angle and distance and launching angle.